Pengeluaran Pemerintah Sektor Pertanian, Produksi dan Kemiskinan Pedesaan di Indonesia - Kharisma, Bayu; Wardhana, Adhitya; Hutabarat, Aldo Febrari (Jurnal Ekonomi Kuantitatif Terapan, 2020)
ABSTRACT The agricultural sector has an important role in economic development and poverty reduction, because the poor population is concentrated in the livelihoods of the agricultural sector. This study aims to determine the effect of government spending on the agricultural sector on agricultural production and poverty reduction in rural areas. The research method used was the Random Effect simultaneous panel which observed 32 provinces in the period of 2014 to 2017 and used the estimation of the Two Stage Least Square model. The results showed that government spending through increasing the quality of roads, subsidized fertilizers, agricultural equipment & machinery significantly affected agricultural production, while agricultural production did not affect rural poverty reduction, but agricultural productivity, income and farmer exchange rates could reduce rural poverty in a way significant. Keywords: government expenditure, agricultural production, rural poverty poverty reductiom